2020
DOI: 10.1037/ppm0000264
|View full text |Cite
|
Sign up to set email alerts
|

The use of social networking sites, body image dissatisfaction, and body dysmorphic disorder: A systematic review of psychological research.

Abstract: The escalation of social networking site (SNS) usage has led to much research examining both the positive and negative implications SNS can have on well-being. However, whilst many studies have investigated the relationship between SNS usage and body image, there remains a paucity of research in regards to SNS usage and Body Dysmorphic Disorder (BDD). A systematic search was undertaken using Web of Science, PsychInfo and PubMed databases to identify SNS usage and patterns, SNS features and mediating factors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 78 publications
3
50
0
1
Order By: Relevance
“…Further, it has been suggested that the increasing amount of posts identified with the hashtag “fitspiration” (i.e., contents shared to promote healthy messages focused on fitness, exercise, eating styles, physical appearance, and weight control) can emphasize unrealistic body image as well as unattainable habits, thus leading to negative feelings in relation to mood, self-esteem, body image and emotional well-being [ 18 , 21 – 25 ]. This can also contribute [ 26 ] to induce in vulnerable users symptoms related to a specific form of body dysmorphic disorder (BDD), the so called muscle dysmorphia (MD), characterized by extreme preoccupation over one’s physical appearance and muscularity and by compulsive physical exercise [ 16 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been suggested that the increasing amount of posts identified with the hashtag “fitspiration” (i.e., contents shared to promote healthy messages focused on fitness, exercise, eating styles, physical appearance, and weight control) can emphasize unrealistic body image as well as unattainable habits, thus leading to negative feelings in relation to mood, self-esteem, body image and emotional well-being [ 18 , 21 – 25 ]. This can also contribute [ 26 ] to induce in vulnerable users symptoms related to a specific form of body dysmorphic disorder (BDD), the so called muscle dysmorphia (MD), characterized by extreme preoccupation over one’s physical appearance and muscularity and by compulsive physical exercise [ 16 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has expanded the scope of inquiry into specific behaviours associated with problematic outcomes beyond time spent engaged in the activity: compulsive texting and diminishing academic performance [ 51 ]; daily interruptions and reduced productivity [ 52 ]; excessive selfie-taking and negative comparisons associated with narcissistic tendencies, disordered eating, body image concerns and body dysmorphic disorder [ 53 , 54 , 55 ]; the experience of fear of missing out (FoMO; missing out on pleasurable activities), and nomophobia (‘no mobile phone’ phobia) [ 56 , 57 ]; compulsive use and checking behaviours [ 58 , 59 ]; exhibiting aggression, cyberbullying and cyberstalking [ 60 ]; phubbing (snubbing an individual by using ones smartphone instead of engaging socially) [ 61 ]; sexting and sext-sharing [ 62 ]; and problematic smartphone use [ 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rodgers' ( 40 ) meta-analysis indicated significant effect sizes of exposure to pro-eating disorder websites on body image dissatisfaction ( d = 41), negative affect, and diet. Furthermore, a systematic review by Ryding and Kuss ( 41 ) showed that appearance-related activity on social media was a stronger predictor of body image disturbances than social media use alone.…”
Section: Introductionmentioning
confidence: 99%